Analysis of Water Quality Parameters in Lhok Bubon Estuary, West Aceh Regency - Ananda, Eva Ersia; Auliana, Nur; Agustia, Desti; Wahyuni, Sri; Hanan, Dendi; Munajar, Munajar; Samudra, Arung; Amelia, Putri (South East Asian Water Resources Management, 2024)
Estuary waters have unique characteristics where fresh water and seawater transition. These characteristics affect the environment's quality and aquatic biota's life. In addition, human activities such as fishing and industry can also affect water quality and impact biota's life. This study aims to analyze water quality parameters in Muara Lhok Bubon, West Aceh Regency waters. This study was conducted in September 2024 and used a survey method. The results showed an average water temperature of 29.9 ° C, an average pH of 7.6, and an average current speed of 0.24 m/s. These parameters indicate that the water quality in Muara Lhok Bubon is still in the good category, supporting the survival of aquatic biota.